2014
DOI: 10.1371/journal.pone.0100292
|View full text |Cite
|
Sign up to set email alerts
|

Upper Girdle Imaging in Facioscapulohumeral Muscular Dystrophy

Abstract: BackgroundIn Facioscapulohumeral muscular dystrophy (FSHD), the upper girdle is early involved and often difficult to assess only relying on physical examination. Our aim was to evaluate the pattern and degree of involvement of upper girdle muscles in FSHD compared with other muscle diseases with scapular girdle impairment.MethodsWe propose an MRI protocol evaluating neck and upper girdle muscles. One hundred-eight consecutive symptomatic FSHD patients and 45 patients affected by muscular dystrophies and myopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
75
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(85 citation statements)
references
References 35 publications
8
75
2
Order By: Relevance
“…In the arms, the anterior compartment is markedly involved. By contrast sternocleidomastoid, pectoralis minor and major and triceps brachii are constantly spared in all cases and sometimes appear to be hypertrophied, differently from other reported myopathies [30]. Taken together, this combination of muscle involvement in lower and upper limbs composes a constant pattern and represents a signature of NLSD-M in all stages of the disease.…”
Section: Discussionmentioning
confidence: 63%
“…In the arms, the anterior compartment is markedly involved. By contrast sternocleidomastoid, pectoralis minor and major and triceps brachii are constantly spared in all cases and sometimes appear to be hypertrophied, differently from other reported myopathies [30]. Taken together, this combination of muscle involvement in lower and upper limbs composes a constant pattern and represents a signature of NLSD-M in all stages of the disease.…”
Section: Discussionmentioning
confidence: 63%
“…The shoulder girdle muscles are smaller and run rather horizontally; such muscles are covered poorly in an MRI protocol consisting of axial and discontinuous slices and therefore are more difficult to analyse. Tasca et al [34] describe in a recent MRI study on the upper extremities without clinical correlation in 108 patients with FSHD that trapezius und serratus anterior muscles are most affected in MRI. Rijken et al showed in their whole-body muscle-CT-based study a similar pattern of muscular affection compared with this study.…”
Section: Other Correlationsmentioning
confidence: 99%
“…Correspondingly, Reilich et al [13] proposed to consider FSHD as a spectrum disorder, especially when histopathology shows vacuolar myopathy. Tasca et al [34] proposed a disease-specific pattern of muscular affection in FSHD.…”
Section: Other Correlationsmentioning
confidence: 99%
“…In most of the MRI studies conducted in FSHD patients, fat infiltration of the investigated muscles has been evaluated visually using the common ordinal scales including 4 to 5 grades [21][22][23][24][25][26]. In these studies muscles from upper limbs [21], lower limbs [22], both upper and lower limbs [23], or from the whole body have been investigated [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…In these studies muscles from upper limbs [21], lower limbs [22], both upper and lower limbs [23], or from the whole body have been investigated [24][25][26]. Although this qualitative scoring is of interest to determine the pattern of muscle involvement, it has been largely recognized as subjective, reader-dependent and lacking sensitivity due to the limited number of grading possibilities.…”
Section: Introductionmentioning
confidence: 99%